IMPLEMENTATION OF COMPREHENSIVE PREVENTION OF DENTAL CARIES IN CHILDREN WITH CEREBRAL PALSY - Mirsalikhova F. L; Eronov Yo. K. (International Journal of Human Computing Studies, 2020)
Over the past decade, the number of disabled children aged 2-14 years with diseases of the central nervous system increased from 11974.6 to 15691.2, an increase of up to 16 percent was observed in cerebral palsy. Children with disabilities all over the world - due to severe functional disorders, and appropriate dental care is provided in kindergartens and schools. cerebral palsy is a complex disease of the nervous system that occurs in the conditions of maturity of the brain, that is, in the process of fetal development, childbirth and the newborn (nikitina 1979), cerebral palsy is characterized by damage to the musculoskeletal system, speech and mental disorders, reduced hearing and vision.